Environmental Education Experience with Students from One Costa Rican Rural School - Sisfontes Guilarte, Pablo (2010)
This article describes a teaching experience developed in Environmental Education in a Costa Rican rural school with students from ninth year, characterized by the dynamics of a workshop in which stresses the participation in the construction of initiatives to address environmental problems detected by the youth in their communities. The article aims to contribute to the construction of a pedagogical model of self-management training and education of young people in environmental sectors, tourism and agriculture, in the conviction that education constitutes a vital alternative for understanding and solving environmental problems.